Adolescent loneliness and psychiatric morbidity in the general population: Identifying "at risk" groups using latent class analysis. (November 2014) - Shevlin, Mark; Murphy, Siobhan; Murphy, Jamie
Abstract Background: Previous research has shown that loneliness is strongly associated with both physical and psychological ill health, particularly among adolescents. Factor analytic research has also shown that loneliness is a multi-dimensional construct, characterized by e.g. feelings of isolation, and relational and collective connectedness. While factor analytic representations of the phenomenon effectively illustrate the structure and form of the loneliness construct, they may not adequately capture its expression in the population within, among and across individuals. Method: The current study modelled the expression of loneliness among a population sample of Northern Irish adolescents using latent class analysis. Data from the Young Life and Times Survey (2011) was used to identify the fewest groups of adolescents in the population characterized by discrete and shared loneliness profiles based on their responses to the UCLA Loneliness Scale (UCLA-LS). Individual "at risk" status for psychiatric morbidity was then assessed on the basis of LCA-group membership. Results: Four groups of adolescents were identified: 1) high loneliness, characterized predominantly by feelings of isolation, 2) intermediate loneliness (two groups), and a baseline group with low levels of loneliness. While all groups were more likely to screen positive for psychiatric morbidity compared with the baseline group, notable risk, however, was attributable to specific isolation experiences or disconnectedness, that characterized both the profiles of the high loneliness group and the similar, but less severe, intermediate loneliness group. Conclusions: Loneliness is distributed throughout the adolescent population; however, among a significant minority, loneliness is predominantly characterized by feelings of isolation and is strongly indicative of psychological ill health.